Enhancing reading strategies through literature selection in EFL classrooms - Durak, Ayşegül; Yavuz, Fatih (Indonesian Journal of Education and Pedagogy, 2024)
This study presents a detailed examination of how to enhance reading strategies with selected literary genres using the library research method. In addition to library resources, the information collection process has been monitored through various academic publications, articles and books, the data obtained has been analysed and the results have been evaluated. Discovering the efficacy of authentic texts demonstrates that it enhances reading comprehension and fosters the abilities of learners. The study also identifies key strategies such as skimming, scanning, guessing, and distinguishing implied and literal meaning strategies. These techniques play a significant role in learners’ capability of understanding authentic text. Drawing on theoretical frameworks, the study underscores the importance of integrating the strategies mentioned above into teaching reading to enrich deeper understanding and critical engagement with literature. As a result, using the selected strategies and literary sources can effectively equip EFL learners to understand the unknown parts of complex texts. Language acquisition and proficiency improvement in authentic text are facilitated by navigating.